Synthesis of furo[2,3-b]pyran-2-ones through Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols and alpha-ketoesters - Thorat, Sagar S.; Kataria, Priyanka; Kontham, Ravindar (Organic Letters, 2018)
Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols (5-hexyn-1-ol systems) with a-ketoesters involving a dual activation process (pi and sigma) has been developed for the first time. This reaction proceeds through cycloisomerization of alkynol to give the 6-endo-enol ether followed by annulation with an alpha-ketoester to furnish furo[2,3-b]pyran-2-ones in good yields. Chemical structures of all products were rigorously confirmed by single crystal X-ray analysis and analogy.

Stereoselective total synthesis of (+/-)-pleurospiroketals A and B - Thorat, Sagar S.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2021)
A full account of our efforts toward the stereoselective total synthesis of sesquiterpenoid-derived natural products (+/-)-pleurospiroketals A and B is described. Commercially available 3-methyl-2-cyclohexenone and 2,2-dimethyloxirane were used as key building blocks, and the substrate-controlled stereoselection was exploited to access the entire stereochemistry of these natural products. Initially, a planned synthetic route involving a [6,5]-bicyclic lactone intermediate was found to be insurmountable, and the later strategy comprising OsO4-NMO-mediated dihydroxylation of 3-methyl-2-cyclohexenone, followed by Luche reduction, Eschenmoser methylenation, and Bronsted acid-induced spiroketalization steps, was ultimately identified as the reliable strategy.

Strategies for the synthesis of furo-pyranones and their application in the total synthesis of related natural products - Thorat, Sagar S.; Kontham, Ravindar (Organic Chemistry Frontiers, 2021)
The furo-pyranone framework is widely present in the molecular structure of various biologically potent natural products and un-natural small molecules, and it represents a valuable target in synthetic organic chemistry and medicinal chemistry. In the last five decades, numerous innovative synthetic methodologies have been disclosed for these bis-oxacyclic fused heterocycles, expanding the scope of accessible building blocks, efficient and affordable catalysis, facile reaction conditions, and overall practicality of the process. In this comprehensive review article, we focus on showcasing the complete spectrum (from the first report in the 1970s to the latest disclosure in 2020) of efforts devoted towards the synthesis of diverse classes of furo-pyranones through systematization and critical analysis of the accumulated experimental knowledge and their elegant applications in total syntheses of biologically interesting related natural products.

Silver-catalyzed [3 + 3]-annulation cascade of alkynyl alcohols and α,β-unsaturated ketones for the regioselective assembly of chromanes - Nakate, Ashwini K.; Thorat, Sagar S.; Jain, Shailja; Rama Krishna, Gamidi; Vanka, Kumar; Kontham, Ravindar (Organic Chemistry Frontiers, 2022)
An unprecedented Ag(i)-catalyzed [3 + 3]-annulation of alkynyl alcohols (5-hexyn-1-ols) and α,β-unsaturated ketones is reported to construct simple to complex chromanes. This transformation begins with hydroalkoxylation of alkynol through C–C triple bond activation to give cyclic-enol ether, followed by intermolecular 1,4-addition and intramolecular 1,2-addition of enol ethers onto the enone and oxidative aromatization or Grob-type elimination steps. Facile reaction conditions, broad substrate scope, good to excellent yields, and atom economy are the salient features of this protocol. Isolation of the active pyran-tethered cyclohexadiene reaction intermediate, additional supporting experiments, and DFT calculations strongly support the experimental findings and corroborate our proposed mechanism.

Studies directed toward the synthesis of hedycoropyrans: total synthesis of des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) - Kataria, Priyanka; Nomula, Rajesh; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2022)
A full account of our efforts directed towards the synthesis of the diarylheptanoid-derived natural products hedycoropyrans that led to the total synthesis of ent-rhoiptelol B is described. In this endeavor, we have attempted two distinct synthetic strategies to access hedycoropyrans A and B, which led us to establish a facile synthetic route for des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) from simple and readily accessible building blocks of 4-allylanisole and vanillin, employing Sharpless asymmetric epoxidation, CBS reduction, and an intramolecular AgOTf-catalyzed oxa-Michael reaction of suitably functionalized hydroxy-ynone as key transformations. The investigations disclosed herein will provide insights into designing novel synthetic routes for THP-DAH-derived natural products.

Studies directed toward the total synthesis of nannocystin A - Nomula, Rajesh; Pratapure, Madhukar S.; Kontham, Ravindar (ChemistrySelect, 2022)
A full account of our efforts directed toward the stereoselective total synthesis of nannocystin A, a macrocyclic myxobacterial metabolite, is presented. In this endeavor, we have attempted two distinct synthetic routes to access polyketide fragment (C1-C11) of macrocyclic depsipeptide (21-membered) natural product from readily accessible building blocks 1,3-propanediol and benzaldehyde employing Evans aldol, CBS reduction, Heck cross-coupling, and Sharpless asymmetric epoxidation as key transformations. Ultimately, accomplished the synthesis of the complete skeleton (21-membered precursor for macrocyclic depsipeptide) of the nannocystin A possessing desired stereochemistry and functional groups.
Keywords: amidation; Depsipeptide; Evans aldol reaction; Macrocycle; Nannocystins

Structure of epoxide hydrolase 2 from Mangifera indica throws light on the substrate specificity determinants of plant epoxide hydrolases - Bhoite, Ashwini; Gaur, Neeraj K.; Palange, Megha; Kontham, Ravindar; Gupta, Vidya; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2024)
Epoxide hydrolases (EHs) are a group of ubiquitous enzymes that catalyze hydrolysis of chemically reactive epoxides to yield corresponding dihydrodiols. Despite extensive studies on EHs from different clades, generic rules governing their substrate specificity determinants have remained elusive. Here, we present structural, biochemical and molecular dynamics simulation studies on MiEH2, a plant epoxide hydrolase from Mangifera indica. Comparative structure-function analysis of nine homologs of MiEH2, which include a few AlphaFold structural models, show that the two conserved tyrosines (MiEH2Y152 and MiEH2Y232) from the lid domain dissect substrate binding tunnel into two halves, forming substrate-binding-pocket one (BP1) and two (BP2). This compartmentalization offers diverse binding modes to their substrates, as exemplified by the binding of smaller aromatic substrates, such as styrene oxide (SO). Docking and molecular dynamics simulations reveal that the linear epoxy fatty acid substrates predominantly occupy BP1, while the aromatic substrates can bind to either BP1 or BP2. Furthermore, SO preferentially binds to BP2, by stacking against catalytically important histidine (MiEH2H297) with the conserved lid tyrosines engaging its epoxide oxygen. Residue (MiEH2L263) next to the catalytic aspartate (MiEH2D262) modulates substrate binding modes. Thus, the divergent binding modes correlate with the differential affinities of the EHs for their substrates. Furthermore, long-range dynamical coupling between the lid and core domains critically influences substrate enantioselectivity in plant EHs.
Keywords: Enantioselectivity; Epoxide hydrolase; molecular dynamics simulation; Regioselectivity; X-ray crystallography

Studies on the stereoselective synthesis of sacubitril via a chiral amine transfer approach - Sadanande, Megha V.; Thorat, Sagar S.; Sharma, Himanshu; Singh, Geetika; Vanka, Kumar; Gonnade, Rajesh G.; Kontham, Ravindar (Chemistry-An Asian Journal, 2025)
We present a comprehensive account of our efforts directed towards the synthesis of sacubitril, a neprilysin inhibitor used in combination with valsartan and marketed as Entresto (TM). Our initial approach to the formal synthesis of sacubitril employed a chiral pool strategy, utilizing (S)-pyroglutamic acid as a key building block and Cu(I)-mediated Csp2-Csp3 cross-coupling as a key transformation. Further investigations led to the development of chiral amine transfer (CAT) reagents-based stereoselective synthesis. This involved the E-selective construction of gamma-ylidene-butenolide from readily available biphenyl bromide and 4-pentynoic acid, the conversion of this butenolide to its ene-lactam using chiral amine, and substrate-controlled diastereoselective reduction of ene-lactam using Et3SiH or Pd/C, H2 (overall chiral amine transfer) as key transformations. Antipodal lactam intermediates were synthesized using corresponding chiral amines, and the stereochemical outcomes during the ene-lactam reduction with Et3SiH were rationalized by DFT studies.
Keywords: Chiral Amine Transfer (CAT) approach; Chiral pool approach; Sacubitril; stereoselective synthesis